What's Hot in Literacy 2018: Going Digital and Disciplinary. Issue 1 (2nd January 2019) - Cassidy, Jack; Ortlieb, Evan; Grote-Garcia, Stephanie
ABSTRACT: The following article explores the "hot topics" in literacy for 2018, keeping the tradition of the "What's hot in literacy" survey that was first published in 1997. Expert panelists from around the globe provided insight into current trends and issues in the field of literacy, resulting in digital and disciplinary literacies being classified as the hottest topics this year. The What's Hot in Literacy 2018 survey aims to keep teachers and educators alike up to date on current literacy research and practice.